What has the WASHES community discussed about Software Economics in the last years? - Araújo, Allysson Allex; Gonçalves, Victor; Farias, Isaac; Santos, Rodrigo; Viana, Davi (Anais do Workshop sobre Aspectos Sociais, Humanos e Econômicos de Software (WASHES); 2024: Anais do IX Workshop sobre Aspectos Sociais, Humanos e Econômicos de SoftwareDO - 10.5753/washes.2024.2999, 2024)
Software Economics concentrates on enhancing the value derived from investments in software development and utilization, making it a critical aspect of decision-making in Software Engineering (SE). As such, this paper delves into the economic aspects of SE through a scope review on the Workshop on Social, Human, and Economic Aspects of Software (WASHES) proceedings. Following Boehm’s seminal roadmap from 2000, we aim to portray advancements, identify emerging trends, and highlight challenges found in the WASHES research landscape over the past nine years. More specifically, this study contributes to academia by consolidating existing knowledge and suggesting future directions for software economics. Our findings offer industry stakeholders a forward-looking perspective on the current state, trends, and challenges in software development processes, enabling proactive strategies to enhance economic efficiency and strategic decisions.